Development and current state of the regulation of the natural exposure of the public of the Russian Federation (To commemorate the 90th birthday of Professor Krisiyk E.M.). Part 1 - V. V. Omelchuk (Радиационная гигиена)
In April 2020 we commemorate the 90th birthday of the major scientist, doctor of technical sciences, Professor Eduard Mechislavovich Krisiyk. A new field of research on radiation-hygienic assessment of the natural sources of ionizing exposure and limitation of the public exposure has been developed under his scientific supervision and personal participation. For the first time in the international practice E.M. Krisiyk as the main author developed the requirements for the concentration of the natural radionuclides in the building materials; as the co-author – in phosphoric fertilizers, indicated the necessity of their radiation control. His scientific results were included into various Russian legislative and methodical documents: Federal state law “On the radiation safety of the public” in 1996, Norms of the radiation safety NRB-96 and NRB-99, Basic sanitary rules on the provision of the radiation safety OSPORB-99, Federal targeted program “Radon”, various guidelines. His scientific school, his flock and followers are successfully developing the scientific-methodical basics of the regulation of the natural exposure of the public of the Russian Federation at the current stage.